Distribuição e classificação dos resíduos sólidos no trato digestório de tartarugas-verdes (Chelonia mydas) e sua associação com as atividades antrópicas. - Liesner, César Oliveira (2021)
Marine pollution is a worrying factor and its consequences can even cause the death of animals that inhabit these places, including sea turtles. The aim of this study was to evaluate the distribution and classification of solid waste in the digestive tract of green turtles (Chelonia mydas) and its association with human activities on the southern coast of Espírito Santo, Brazil. For this, three experiments were carried out, namely: a) evaluation of the gastrointestinal tracts of green turtles found naturally dead on the southern coast of Espírito Santo; b) epidemiological survey of fishermen from Espírito Santo on the possible influence of fishing activities and its impacts on marine life; and c) assessment and measurement of the amount of marine litter on the beaches of the southern coast of Espírito Santo. The study site involved the municipalities of Guarapari, Anchieta, Piúma and Itapemirim do Espírito Santo. Ingestion of anthropogenic residues was observed in the digestive tract of 71% (24/34) of the evaluated turtles, recording 286 fragments of residues and 98.83 grams. Regarding the epidemiological survey with fishermen, 60% of the interviewees said that the accidental captures of turtles take place in fishing nets and, with regard to environmental perception, 81% of the interviewees said they observed waste in the sea. Were collected 41Kg of waste in the eight beaches evaluated and 88 different different items. It is concluded that the distribution of residues in the digestive tract of green turtles is more frequent in the large intestine, with plastic being the main type found. Fishermen do not consider the fishing activity as the main source of threat to marine animals, at the same time, they understand that the presence of waste in the oceans is harmful and attribute this pollution to the local population and beachgoers. The amount of waste found on the beaches of the Espírito Santo coast is relevant and, therefore, it is important and urgent to implement public policies for this environmental problem, which requires society's education to review its consumption and behavior patterns.